Pendampingan Diskusi Kelompok Kecil Guna Menumbuhkan Motivasi Belajar Siswa Kelas II SDN 28 Mataram - Chairunnisa, Lulu (Jurnal Pengabdian Masyarakat Sains Indonesia, 2024)
This service to the community is motivated by observations that show students' lack of interest and enthusiasm for learning during the learning process. There are several things that influence students' interest and enthusiasm to decrease, including less effective learning models and methods and a lack of approach or attention given by educators during the learning process. The learning process should be able to encourage students to always be active in interaction and communication between educators and other students so that the learning process can run effectively. There are several goals to be achieved in this service, including increasing the learning motivation of class II students at SDN 28 Mataram through accompanying small group discussions and it is hoped that these students can always be active in the learning process. The method used in this service is the service learning method with three stages, namely; planning stage, implementation stage, and reflection stage. The results of the mentoring show that the implementation of activities from the initial stage to the final stage went well, students began to be interested in participating in the learning process and showed an attitude of confidence, enthusiasm and motivation to learn.